ITCs for the management of learning in health: Drug services in the Americas - García, Óscar Felipe (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study aimed to analyze experiences that consider ICTs in the management of learning in health and to identify some components that can facilitate a management mechanism to promote training and knowledge development for the care of drug use, abuse, and dependence from the perspective of evidence-based learning. To carry out this work, a community-based research methodology has been used, through an educational project with drug learning communities with 200 people from countries in the Americas such as Colombia, Mexico, Panama, Chile, and Paraguay.